Temperature Dependence of the Isosteric Heat of Adsorption - D.V. Cao; S. Sircar (Adsorption Science & Technology)
Direct calorimetric measurements of the isosteric heats of adsorption of (a) pure CO 2 on a strongly heterogeneous adsorbent (silicalite with an alumina binder) and (b) pure N 2 on a mildly heterogeneous adsorbent (5A zeolite) at different temperatures and adsorbate loadings demonstrated the validity of the conventional assumption that isosteric heats are very weak functions of temperature. A simple thermodynamic model for the adsorption of a pure gas on an adsorbent containing two different energetic sites also validated the same assumption in the Henry's law region.